Bhutan - A Search for Happiness - Barabas, Pavol (K2 Studio, 2008)
Verzio FF Submission It's said that Bhutan was forgotten by people but never by the Gods. The natives call this ancient mountain kingdom, squeezed between Indian Assam and Chinese Tibet, the land of the Thunder Dragon. Wandering through a forgotten country in which people worship all living things is a story of happiness. Internal peace is valued here more than a craving for worldly pleasures, and harmony with nature is the supreme principle. A good king cares for the wealth of his people. Instead of Gross Domestic Product, he promotes Gross National Happiness. In its fragile perception of happiness, this small Himalayan kingdom has chosen to follow a strange path. Maybe its the right one. This documentary illustrates life as it is understood and lived in Bhutan.